In Silico Screening of Phytochemicals Targeting SmdCD of Streptococcus mutans using Molecular Docking Approach - Pundir, Hemlata; Pathak, Ramanand; Pant, Tanuja; Pant, Manish; Chandra, Subhash; Tamta, Sushma (Trends in Sciences, 2023)
Introduction: Dental caries is a chronic infectious disease caused by bacteria forming a biofilm formation on the tooth surface. Drug-resistant bacteria Streptococcus mutans (S. mutans) pose a vital public health issue. To overcome this, the development of effective drugs with a novel mechanism of action is very important. Drug repurposing is considered a viable alternative approach to overcome the above issue. In the present study, we have attempted to select unique and traditional source used as in traditional medicine. To continue this effort, in this study we used phytochemical of selected to find an effective cure for dental caries. Materials and methods: Inhibition of S. mutans deoxycytidylate deaminases (SmdCDs) is a promising drug development strategy against S. mutans, responsible for biofilm formation. Since no effective drugs are available against S. mutans, we conducted a virtual screening of phytochemicals to find novel compounds against this bacterium. Hence, we created a library of 871 phytochemicals from 13 plants with reported antimicrobial activity. The phytochemical library was subjected to virtual screening against the SmdCD target. Results and discussion: Traditionally, many cultures use chewing sticks for oral hygiene maintenance. In the present work, out of 871 phytochemicals, 211 phytochemicals showed the most druggable substance with zero violation from any of the drug-likeness rules. Further, the binding energy indicates the affinity of adhesion of protein structure docked with 2 hit potential herbal compounds of which Cyclocurcumin and Androsta-1,4,6-triene-3,17-dione showed the best docking with SmdCD. Conclusions: Based on the binding energy score, we suggest that hit compounds can be used for dental caries and further could be developed as an organic mouthwash. HIGHLIGHTS Streptococcus mutans is common in the human oral cavity and contributes significantly to tooth decay mutans deoxycytidylate deaminases (SmdCDs) are responsible for biofilm formation causing drug resistance SmdCDs can be used to develop effective drug against mutans, responsible for biofilm formation Screening phytochemicals may result potential compounds which can be used to develop new drugs against mutans GRAPHICAL ABSTRACT